Identificação perceptivo-auditiva de contrastes de obstruintes por crianças com e sem Transtorno Fonológico - Assis, Mayara Ferreira de; Cremasco, Elissa Barbi Mouro Pagliari [UNESP]; Domingues, Isabella Rodrigues [UNESP]; Berti, Larissa Cristina [UNESP] (FapUNIFESP (SciELO), 2025)
PURPOSE: (1) To compare auditory-perceptual accuracy and reaction time in children with and without phonological disorders for identifying the contrast of obstruents, and (2) to verify whether there is an effect of the phonetic class (stops vs. fricatives) on the accuracy, reaction time and error pattern. METHODS: Sixty-two children (41 diagnosed with phonological disorders and 21 with typical phonological development), aged between 4 and 9 years, participated in the study. An identification task was performed in the obstruent class using the speech perception assessment instrument (PERCEFAL). Reaction time, percentage of correct and incorrect answers, and the error pattern were considered in the analysis. Results: Regarding auditory-perceptual accuracy, children with phonological disorders had a significantly lower average of correct answers than children with typical phonological development for both obstruent classes. Regarding reaction time, children with phonological disorders showed longer reaction times for the stop class (p≤0.05). In the error pattern analysis, errors involving the articulatory point were the most frequent for both classes and both groups of children. CONCLUSION: The presence of phonological disorders implies attenuated perceptual accuracy. The longer reaction time of children with phonological disorders depends on the phonic class.

OBJETIVO: (1) comparar a acurácia perceptivo-auditiva e o tempo de reação em crianças com e sem transtorno fonológico na identificação do contraste das obstruintes; (2) verificar se há um efeito da classe fônica (oclusivas vs fricativas) na acurácia, no tempo de reação e no padrão de erro. MÉTODO: Participaram do estudo 62 crianças (41 com diagnóstico de transtorno fonológico e 21 com desenvolvimento fonológico típico), entre 4 a 9 anos de idade. Foi realizada uma tarefa de identificação na classe das obstruintes, a partir do instrumento de avaliação de percepção de fala (PERCEFAL). O tempo de reação, a porcentagem de erros e acertos, bem como o padrão de erro foram considerados na análise. RESULTADOS: Com relação à acurácia perceptivo-auditiva, as crianças com transtorno fonológico tiveram uma média de acerto significativamente inferior quando comparadas às crianças com desenvolvimento fonológico típico, para ambas as classes. Quanto ao tempo de reação, as crianças com transtorno fonológico apresentaram maior tempo de reação para a classe das oclusivas (p≤0,05). Na análise do padrão de erro, os erros envolvendo o ponto articulatório foram os mais frequentes para ambas as classes e para ambos os grupos de crianças. CONCLUSÃO: A presença do transtorno fonológico implica em menor acurácia perceptual. O maior tempo de reação das crianças com transtorno fonológico é dependente da classe fônica.
Identification of obstruent contrasts by children with and without phonological disorders